Assessment of terminal heat tolerance among wheat (Triticum aestivum) genotypes based on multivariate analysis and selection indices - BARANWAL, DEEPAK; KUMAR, ROUNAK; AZAD, C S; MUNJAL, RENU (The Indian Journal of Agricultural Sciences, 2024)
Terminal heat stress is of major concern for global wheat (Triticum aestivum L.) production as wheat prefers a cool climate. Using physiologically efficient parents in crossing programme and direct selection of elite genotypes would be useful for breeding climate-resilient wheat. A field experiment was conducted during winter (rabi) season of 2021–22 at Bihar Agricultural College, Sabour, Bhagalpur, Bihar to study the terminal heat tolerance among wheat genotypes based on multivariate analysis and selection indices. A set of 225 wheat genotypes was evaluated under normal sowing (Timely sown) and heat stress conditions (Late sown) during 2021–22 to perform multivariate analysis, viz. D2 statistics, principal component analysis and selection indices, heat susceptible index (HSI) for grain filling duration, 1000-grain weight and yield. The clustering pattern as per Tocher’s optimization method and magnitude of D2 value revealed that wheat genotypes studied for 16 traits were grouped into seven clusters, where cluster V with 51 genotypes emerged as the largest cluster. Cluster VII and cluster III showed highest inter-cluster distance (6.958). HSI for grain filling duration (GFD), 1000 grain weight (TGW) and yield per plot (YPPT) ranged from 0.36 (genotype 30, GID: 7933202) to 2.51 (genotype 54, GID: 7933656), -0.84 (genotype 44: GID: 7933473) to 2.66 (genotype 36, GID: 7933333) and -0.49 (genotype 37 GID: 7933334) to 1.93 (genotype 49, GID: 7933509), respectively. Genotypes 88, 74 and 66 showed low HSI for GFD, TGW and YPPT, respectively. Six principal components (PC1 to PC6) accounted for 76.38% of the total variation and represented the core traits for further investigation. Identified promising lines and potential donors for yield components like genotype 24 (GID: 7933122), genotype 64 (GID: 7933762), genotype 71 (GID: 7933792), genotype 93 (GID: 7933947) and genotype 172 (GID: 7934632) could be utilized in the crossing programme to breed terminal heat-tolerant wheat.